Opportunities To Achieve Effective Results In International Research By Working On Text In Primary School Reading Lessons. - Melikuzieva Nigora (Research Parks Publishers, 2022)
This article covers general secondary schools and elementary schools on the preparation of students for the PIRLS international assessment system information is provided. It also outlines the steps that need to be taken